Pectin and Kaolin as Adjunctive Metabolic Therapy for Maintaining Remission in Ulcerative Colitis: Biological Rationale, Current Evidence and Future Clinical Perspectives - John K. Triantafillidis; Andreas Panayiotou; Apostolos E. Papalois (Nutrients, 2026)
Background: Ulcerative colitis (UC) is a chronic relapsing inflammatory bowel disease in which long-term maintenance of remission remains a major therapeutic challenge. Increasing evidence indicates that disruption of host–microbiome metabolic interactions, impaired production of short-chain fatty acids (SCFAs), defective epithelial energy metabolism, and intestinal barrier dysfunction contribute to disease relapse. These observations have generated interest in adjunctive metabolic strategies aimed at restoring luminal homeostasis rather than directly suppressing inflammation. Objective: This narrative review examines the biological rationale for combining pectin, a fermentable dietary fiber that promotes endogenous SCFA production, with kaolin, naturally occurring adsorbent clay, as adjunctive metabolic therapy for maintaining remission in UC. We summarize current mechanistic, experimental, and clinical evidence and discuss future translational research priorities. Evidence: Experimental studies demonstrate that pectin fermentation enhances the production of butyrate and other SCFAs, thereby improving epithelial energy metabolism, strengthening intestinal barrier integrity, and modulating mucosal immune responses. Kaolin possesses adsorptive and barrier-protective properties that may reduce luminal exposure to potentially harmful microbial products while improving stool consistency. Although direct clinical evidence supporting the combined use of pectin and kaolin in UC is currently lacking, indirect evidence derived from microbiome research, SCFA biology, dietary intervention studies, and experimental models provides a biologically plausible foundation for further investigation. Perspective: We propose that restoration of luminal metabolic homeostasis through complementary modulation of microbial fermentation and luminal environmental stabilization may represent a novel adjunctive approach for reducing relapse risk in selected patients with UC receiving conventional maintenance therapy. A conceptual framework for future randomized clinical trials incorporating clinical, endoscopic, microbiome, metabolomic, and biomarker outcomes is presented. Conclusions: Current evidence supports the biological plausibility of SCFA-directed metabolic interventions in UC but remains insufficient to justify routine clinical application of pectin–kaolin therapy. Well-designed randomized controlled trials are required to determine efficacy, safety, optimal patient selection, and mechanisms of action. By integrating advances in microbiome science, intestinal metabolism, and mucosal immunology, this review provides a translational framework for the development of inexpensive, microbiome-oriented adjunctive therapies for maintenance of remission in UC.